2017
DOI: 10.1098/rstb.2016.0111
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in visual motion perception and neurotransmitter concentrations in the human brain

Abstract: One contribution of 15 to a theme issue 'Auditory and visual scene analysis'. Recent studies have shown that interindividual variability can be a rich source of information regarding the mechanism of human visual perception. In this study, we examined the mechanisms underlying interindividual variability in the perception of visual motion, one of the fundamental components of visual scene analysis, by measuring neurotransmitter concentrations using magnetic resonance spectroscopy. First, by psychophysically ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 48 publications
2
18
1
Order By: Relevance
“…First, it is consistent with the overall trend from a number of studies of resting state activity [86,87], showing a coarser outcome: they reveal greater variability in regions of the brain associated with more cognitive processing, than regions associated with perceptual processing. Second, it is consistent with studies of perceptual bistability indicating that there may be greater individual variability in the balance of excitation and inhibition in regions associated with more cognitive processing [27,29,85]. Third, it is consistent with the prevalence of evidence supporting the role of more general, higher-level processing stages during perceptual bistability [4,7,20,33,[51][52][53][54][55][56][57][58]; if these higher-level sources play a more dominant role in perceptual bistability, this could be due to the greater variety of configurations at later stages of analysis that can generate perceptual bistability.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…First, it is consistent with the overall trend from a number of studies of resting state activity [86,87], showing a coarser outcome: they reveal greater variability in regions of the brain associated with more cognitive processing, than regions associated with perceptual processing. Second, it is consistent with studies of perceptual bistability indicating that there may be greater individual variability in the balance of excitation and inhibition in regions associated with more cognitive processing [27,29,85]. Third, it is consistent with the prevalence of evidence supporting the role of more general, higher-level processing stages during perceptual bistability [4,7,20,33,[51][52][53][54][55][56][57][58]; if these higher-level sources play a more dominant role in perceptual bistability, this could be due to the greater variety of configurations at later stages of analysis that can generate perceptual bistability.…”
Section: Discussionsupporting
confidence: 83%
“…The results also indicate that there are more variations of the later stages consistent with human data than earlier stages of processing. When interpreted in light of the significant individual differences found in perceptual bistability [21][22][23][24][25][26][27][28][29]85], a possible implication is that there is greater variability in human function for the higher-level stages of auditory processing, than lower-level stages of processing. April 3, 2019 13/28…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Duncan and Boynton (2003), found that the cortical magnification factor in primary visual cortex correlates with visual acuity. Recent work (see Kanai & Rees, 2011 for a review) has revealed correlations between brain structure and biological motion detection (Gilaie-dotan, Kanai, Bahrami, Rees, & Saygin, 2013), rate of perceptual alternation in binocular rivalry (Kanai, Bahrami, & Rees, 2010), motion assimilation and contrast (Takeuchi, Yoshimoto, Shimada, Kochiyama, & Kondo, 2017), susceptibility to geometrical illusions (Axelrod, Schwarzkopf, Gilaie-dotan, & Rees, 2017; Schwarzkopf, Song, & Rees, 2011), susceptibility to the tilt illusion (Song, Schwarzkopf, & Rees, 2013b; Song et al, 2013a), and orientation discrimination (Song et al, 2013b). …”
Section: The Value Of Research On Individual Differencesmentioning
confidence: 99%
“…In contrast, in this issue, Takeuchi et al [19] observed a relationship between the concentration of Glx and visual motion perception only in the prefrontal cortex and not in visual areas. They examined two types of motion phenomena-motion assimilation and contrast-and found that, following the presentation of the same stimulus, some participants perceived motion contrast, whereas others perceived motion assimilation.…”
Section: Individual Differences In Auditory and Visual Scene Analysismentioning
confidence: 78%